2011
DOI: 10.1007/s10531-011-0112-2
|View full text |Cite
|
Sign up to set email alerts
|

Grazing effects on plant functional group diversity in Mediterranean shrublands

Abstract: Grazing is one of the prevalent human activities that even today are taking place inside protected areas with direct or indirect effects on ecosystems. In this study we analyzed the effects of grazing on plant species diversity, plant functional group (PFG) diversity and community composition of shrublands. We analyzed plant diversity data from 582 sampling plots located in 66 protected areas of the Greek Natura 2000 network, containing in total 1102 plant species and subspecies. We also classified a priori al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 50 publications
2
28
2
1
Order By: Relevance
“…EEA's's (2015b) "State of nature in the EU" reports that farmland bird populations continue to decline. On one hand, some traditional agricultural activities, such as grazing and mowing, may be essential for maintaining and restoring some habitats and associated species and thus should be incorporated into management plans of N2k sites (Halada et al, 2011;Papanikolaou et al, 2011;Faria et al, 2012;Arponen et al, 2013). On the other hand, some practices such as intensification of cultivation or use of pesticides may pose threats to biodiversity in the conservation network (EEA, 2015b).…”
Section: Habitat Typesmentioning
confidence: 99%
“…EEA's's (2015b) "State of nature in the EU" reports that farmland bird populations continue to decline. On one hand, some traditional agricultural activities, such as grazing and mowing, may be essential for maintaining and restoring some habitats and associated species and thus should be incorporated into management plans of N2k sites (Halada et al, 2011;Papanikolaou et al, 2011;Faria et al, 2012;Arponen et al, 2013). On the other hand, some practices such as intensification of cultivation or use of pesticides may pose threats to biodiversity in the conservation network (EEA, 2015b).…”
Section: Habitat Typesmentioning
confidence: 99%
“…This suggested that functional diversity and species richness were interrelated with each other [25,28]. Each species should have some special functional traits, therefore the greater the number of species in a community is, the greater the change of functional traits and the greater the functional diversity are [6].…”
Section: Discussionmentioning
confidence: 99%
“…which affect plant and community growth and development [15,23]. The effects of aspect and litter thickness on functional diversity were not significant because Acanthopanax senticosus lived in forest under canopy where litters and aspect were consistent [11,28].…”
Section: Discussionmentioning
confidence: 99%
“…Phosphate application, favouring the relative competitive plants, was associated with increased between-year seed dormancy. In a meta-study of 582 plots across Greece, Papanikolaou et al, (2011) found short-lived species (including annual legumes) benefited from grazing and proportion in the community increased with grazing. Pierce, Luzzaro, Caccianiga, Ceriani, and Cerabolini (2007) found that grazing suppresses potentially dominant species and favours diversity.…”
Section: Discussionmentioning
confidence: 99%